Preparatiion of CaO-based pellet using rice husk ash via granulation method for potential CO2 capture - Mohd Daud, Farah Diana; Mohamad Azir, Muhammad Mirza; Mahmud, Mudrikah Sofia; Sarifuddin, Norshahida; Mohd Zaki, Hafizah Hanim (IIUM Press, 2021)
CO2 capturing has become very significant option to reduce the emission of CO2 in the atmosphere and hence, minimizing environmental issues. Among solid CO2 sorbent, calcium oxide (CaO) is an attractive regenerable sorbent for CO2 capturing because of their reactivity and high CO2 absorption capacity. CaO alone suffers from rapid decay of CO2 adsorption during multiple carbonation/calcination reaction cycles. The stability of CaO sorbents during cyclic runs can be achieved via the incorporation of additive support materials. The silica (SiO2) from natural sources such as rice husk is the best candidate to be used as an additive in the sorbents. However, the CaO-based sorbent in finely generated powders are prone to severe attrition problems. Therefore, this research focuses on preparation of CaO-based pellets by using rice husk ash (RHA) via granulation method. The result of the raw materials confirmed that Ca(OH)2 have crystalline structure with finely distributed grains and RHA exhibit amorphous structure with randomly oriented size grains. Based on the XRD, it is confirmed that the insertion of RHA does not alter the phase structure of the pellets. Each ratio yield different intensity value and has formation of new peaks after sintering. Meanwhile, the microstructures of the pellets show that the pores reduced as the calcination temperature increased while the incorporation of RHA caused the pores size increased with randomly oriented shape. These findings indicate that the optimum value for the pellets is with the Ca(OH)2:RHA ratio of 80:20 and calcination temperature of 750 °C.